Hepatitis A seroprevalence in South Africa: Are we in epidemiological transition? - Enoch, Annabel (Division of Virology, 2018)
Hepatitis A virus (HAV) is the most common cause of viral hepatitis worldwide. Infection with HAV is vaccine preventable, however, a vaccine against HAV is not included in the Expanded Programme on Immunization in South Africa (SA). South Africa was considered to be a high endemic country for hepatitis A in the past, hence there was no need for routine immunization against the virus. Our hypothesis is that SA is changing from high to intermediate endemic setting for hepatitis A. To test our hypothesis, we conducted a cross-sectional seroprevalence study in the 1-7 year age group in the Western Cape Province. Our samples for this study were from specimens, collected between August and October 2015, sent for routine diagnosis to referral hospitals in the Western Cape Province. We tested remaining serum of 482 samples sent for routine tests. A Siemens enzyme immunoassay was used to test for hepatitis A antibodies. We also analysed hepatitis A test results from the National Health Laboratory Services (NHLS) Disa*Lab database at Groote Schuur hospital from 2009-2014, as well as hepatitis A surveillance data from the National Institute for Communicable Diseases (NICD) from 2009-2014, to look at the past hepatitis A prevalence trend. Our cross-sectional study showed the seroprevalence to be 44.1% in the 1-7 year age group. The NHLS data showed a seroprevalence of <90% up to age 10 years, indicating intermediate endemicity. The NICD data showed that a substantial number of symptomatic hepatitis A infections occurred in the 7-40 year age group, suggesting an increasing proportion of a susceptible population to HAV infection. Taken together, these results indicate the need for further studies designed to aid the development of vaccination policies against HAV infection in South Africa.